Commercial property tax in the UK: business rates and rating appeals. Issue 6 (5th September 2016) - Greenhalgh, Paul Michael; Muldoon-Smith, Kevin; Angus, Sophie
Abstract : Purpose: The purpose of this paper is to investigate the impact of the introduction of the business rates retention scheme (BRRS) in England which transferred financial liability for backdated appeals to LAs. Under the original scheme, business rates revenue, mandatory relief and liability for successful appeals is spilt 50/50 between central government and local government which both share the rewards of growth and bear the risk of losses. Design/methodology/approach: The research adopts a microanalysis approach into researching local government finance, conducting a case study of Leeds, to investigate the impact of appeals liability and reveal disparities in impact, through detailed examination of multiple perspectives in one of the largest cities in the UK. Findings: The case study reveals that Leeds, despite having a buoyant commercial economy driven by retail and service sector growth, has been detrimentally impacted by BRRS as backdated appeals have outweighed uplift in business rates income. Fundamentally BRRS is not a "one size fits all" model – it results in winners and losers – which will be exacerbated if local authorities get to keep 100 per cent of their business rates from 2020. Research limitations/implications: LAs' income is more volatile as a consequence of both the rates retention and appeals liability aspects of BRRS and will become more so with the move to 100 per cent retention and liability. Practical implications: Such volatility impairs the ability of local authorities to invest in growth at the same time as providing front line services over the medium term – precisely the opposite of what BRRS was intended to do. It also incentivises the construction of new floorspace, which generates risks overbuilding and exacerbating over-supply. Originality/value: The research reveals the significant impact of appeals liability on LAs' business rates revenues which will be compounded with the move to a fiscally neutral business rates system and 100 per cent business rates retention by 2020.